The Power of Operators to Modify the Tourist Trip Elements - Latif, Adnan Baqi (Journal of Legal and Political Studies, 2020)
The tourist as a consumer procuring the anticipated enjoyment and entertainment from the tourist trip is related to the good implementation of all the obligations on the trip organizer’s side in accordance with the terms of contract undertaken between them. In cases where the latter amends some elements of the trip agreed upon, whether prior or during the implementation of the contract; consequently, exploiting the general rules and some rules related to tourism activity. Although this allows trip organizer to depart from the principle of the binding force of the contract with the agreement of the parties, or even without obtaining the approval of the tourist for reasons established by law, as well as, as a professional, the trip organizer enjoys economic, technical, knowledge capabilities and qualifications its capacity as superior to the other party and hence; on the one hand, the resulting imbalance in the contractual relationship in light of the tourist’s lack of legal awareness necessary to comprehend the terms of the contract and how to defend his or her rights before the judiciary, and on the other hand; the absence of legal regulations of tourism contracts and limited protection of tourists in some laws, including the Iraqi law that contains general rules proved as inefficient provisions. Hence, the sentiment of the tourist as a consumer not enjoying legal security as a result of what some of the tour operators organize by altering the elements of the trip by individual will in the context of deception and manipulation, has led the research article to study and explore the deficiencies and the legislative defect from which illicit financial gains are achieved at the expense of the tourist. and, this research article aims to protect the tourist as a consumer from losing the rights entitled to, and to receive fair compensation whenever this is a justified order, additionally, to return some measures of balance to the unequal relationship between the two parties.
Keywords: consumer; tourist trip; obligations; binding force; compensation